O Programa Fome Zero sob Foco - Tiburcio, James Augusto Pires (Sustainability in Debate, 2015)
Aaron Ansell. Zero Hunger: Political Culture and Antipoverty Policy in Northeast Brazil. Chapel Hill, The University of North Carolina Press, 2014. 239 p. Anexos, referências bibliográficas, índice remissivo, ilustrações. ISBN 978-1-46961397-0 .